2016
DOI: 10.3892/mmr.2016.5684
|View full text |Cite
|
Sign up to set email alerts
|

Low mutation percentage of KRAS and BRAF genes in Brazilian anal tumors

Abstract: Anal cancer is a rare type of digestive tract disease, which has had a crescent incidence in a number of regions. Carcinomas are most frequently found, with squamous cell carcinoma (SCC) comprising ~95% of all anal tumors. The major risk factor for development of this type of tumor is human papillomavirus (HPV) infection. However, previous studies have identified patients with anal cancer that are HPV‑/p16‑and observed that they have a poorer outcome compared with HPV+/p16+ patients. This suggests that molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…This supports the findings of a previous study that compared the overall survival and prognosis of patients with anal adenocarcinoma, SCC and rectal adenocarcinoma, in which the authors demonstrated a poorer overall survival rate and prognosis for patients with anal adenocarcinoma (28). This same trend was described by our group in a previous study (24). Furthermore, when considering patient age, the present study identified poorer survival rates in patients ≥67 years old compared with in younger patients (≤47 years old), supporting the results presented by a prior study that revealed younger patients experienced improved overall-and disease-free survival rates compared with older patients with anal cancer (29).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This supports the findings of a previous study that compared the overall survival and prognosis of patients with anal adenocarcinoma, SCC and rectal adenocarcinoma, in which the authors demonstrated a poorer overall survival rate and prognosis for patients with anal adenocarcinoma (28). This same trend was described by our group in a previous study (24). Furthermore, when considering patient age, the present study identified poorer survival rates in patients ≥67 years old compared with in younger patients (≤47 years old), supporting the results presented by a prior study that revealed younger patients experienced improved overall-and disease-free survival rates compared with older patients with anal cancer (29).…”
Section: Discussionsupporting
confidence: 92%
“…A number of previous studies have demonstrated that RKIP expression has prognostic value in several tumor types, including gastric, colorectal and gastrointestinal stromal tumors (17)(18)(19). However, other studies have identified a number of molecular distinctions between anal canal tumors and their colorectal counterparts (24,27). Therefore, the present study aimed to evaluate RKIP expression in invasive and in situ tumors of the anal canal, and to correlate findings with the clinicopathological data.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations